PHOTOPOLARIMETRY OF SOME MIRA-TYPE STARS - Efimov, Yu. S.; Kudashkina, L. S. (Одеські астрономічні публікації, 2017)
The variations of the polarization parameters of three Mira-type stars V CrB, S CrB, T Her in the UBVRI bands are presented.